A dictionary of neurological signs - Larner, A. J. (Springer, 2011)
The first two editions of A Dictionary of Neurological Signs were very well-received by readers and reviewers alike. Like those editions, this Third Edition, updated and expanded, can be almost as well described in terms of what the book is not, along with details about what it is. The Dictionary is not a handbook for treatment of neurological disorders. While many entries provide the latest treatment options, up-to-the-minute therapies are not discussed in bedside level detail. The Dictionary is not a board review book because it is not in Q&A format but could easily serve in that capacity since each entry is a fairly complete snapshot of a specific disorder or disease. The Dictionary is an alphabetical listing of commonly presenting neurological signs designed to guide the physician toward the correct clinical diagnosis. The Dictionary is focused, problem-based, concise and practical. The structured entries in this practical, clinical resource provide a thumbnail of a wide range of neurological signs. Each entry includes: A definition of the sign; A brief account of the clinical technique required to elicit the sign; A description of the other signs which may accompany the index sign; An explanation of pathyophysiological and/or pharmacological background; Differential diagnosis; Brief treatment details Where known, these entries also include the neuroanatomical basis of the sign. A Dictionary of Neurological Signs, Third Edition, is an indispensable reference for all students, trainees, and clinicians who care for patients with neurological disorders.